2020
DOI: 10.3386/w26834
|View full text |Cite
|
Sign up to set email alerts
|

Language Training and Refugees' Integration

Abstract: Social and economic integration of refugees are key to their personal success and to producing positive effects in the host country. We evaluate the effects of a reform that substantially expanded language training for immigrants who obtained refugee status in Denmark on or after January 1, 1999. The same reform also temporarily decreased welfare benefits for a subgroup of them. Using a regression discontinuity design around the cutoff date we find positive and significant employment and earnings effects on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 17 publications
2
36
0
1
Order By: Relevance
“…While life satisfaction of refugees with poor language skills declines over time, it increases among refugees with good or very good German skills at the first interview. This finding might indicate that skills in the language of the destination country are a crucial precondition for integration in the receiving societya finding in line with the prior literature on refugees (van Tubergen, 2010;Arendt et al, 2020).…”
Section: Development Of Refugees' Life Satisfaction and Self-rated Health Over Time And The Role Of Postarrival Experiencessupporting
confidence: 89%
“…While life satisfaction of refugees with poor language skills declines over time, it increases among refugees with good or very good German skills at the first interview. This finding might indicate that skills in the language of the destination country are a crucial precondition for integration in the receiving societya finding in line with the prior literature on refugees (van Tubergen, 2010;Arendt et al, 2020).…”
Section: Development Of Refugees' Life Satisfaction and Self-rated Health Over Time And The Role Of Postarrival Experiencessupporting
confidence: 89%
“…For example, many studies show important associations between language skills and employment outcomes, 5 but only a few utilize exogenous variation. Exceptions include Lochmann et al (2019), Sarvimäki and Hämäläinen (2016) and Arendt et al (2020). Lochmann et al (2019) study the effects of language training in France and find positive effects on labor force participation, where the discontinuity originates from test scores on an initial language exam.…”
Section: Introductionmentioning
confidence: 99%
“…Using a discontinuity originating from a reform, Sarvimäki and Hämäläinen (2016) find increased earnings for unemployed immigrants receiving more language training. Arendt et al (2020) use exogenous variation created by a Danish reform to study effects of improved and more intensive language training. While their point estimates indicate positive effects on earnings over an eighteen year period for treated individuals, their estimated standard errors are relatively large.…”
Section: Introductionmentioning
confidence: 99%
“…5 Several studies (see, for example, Edin et al (2003), Damm (2009), and Beaman (2012)) have found that living in regions with high concentrations of co-ethnic individuals can improve refugees' labor market outcomes. Arendt et al (2020) analyze the impact of an expansion of language training for refugees in Denmark. They show that, after eighteen years refugees who received more and better language training were more likely to be in employment and had higher earnings.…”
Section: Introductionmentioning
confidence: 99%